2022
DOI: 10.3389/fpsyt.2022.879598
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Mental Health During the COVID-19 Pandemic: A Systematic Review

Abstract: ObjectivesThe COVID-19 pandemic raised significant concerns related to the management of care for people with dementia, but few studies have examined the mental health of older adults with dementia and their caregivers during the pandemic, when compared to other populations. This systematic review thus aims to compare and discuss the impact of the COVID-19 pandemic on people with dementia and on their caregivers' mental health.MethodsA search was performed in the PubMed/Medline and ISI databases according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
(215 reference statements)
2
8
0
Order By: Relevance
“…The outcomes of our in‐depth qualitative approach align well with quantitative findings as reviewed by Ahmed et al 23 ; they observed a lack of a clear exacerbation in symptoms of various psychiatric disorders. Participants in our study reported a fairly stable mental health situation, but also a negative impact of the COVID‐19 pandemic and associated restrictions on their overall well‐being.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The outcomes of our in‐depth qualitative approach align well with quantitative findings as reviewed by Ahmed et al 23 ; they observed a lack of a clear exacerbation in symptoms of various psychiatric disorders. Participants in our study reported a fairly stable mental health situation, but also a negative impact of the COVID‐19 pandemic and associated restrictions on their overall well‐being.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast to these negative effects of the COVID‐19 pandemic, a recent quantitative review found no clear pattern of change in mental health symptom severity and associated outcomes in adults with pre‐existing mental health conditions 23 . This systematic review included 37 quantitative studies reporting on one or more of the following outcome measurements: symptom severity, social functioning (assessed through self‐administered questionnaires on social participation and loneliness), quality of life, suicide behaviours and self‐harm in people with pre‐existing mental health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Existing reports indicate that the COVID-19 pandemic has posed significant social, psychological, emotional, and physical challenges to family members and friends who provide care for people with dementia. [604][605][606][607][608][609] Fatigue and burnout among dementia caregivers and their lack of access to services and supports for themselves and for the people for whom they provide care are common themes in research on the wide-ranging effects of the COVID-19 pandemic. For these reasons the pandemic has created a crisis for dementia caregivers.…”
Section: Covid-19 and Dementia Caregivingmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses reported an association between dementia and mortality of COVID-19 ( Dadras et al, 2022 , Hariyanto et al, 2021 , July and Pranata, 2021 , Liu et al, 2020 , Saragih et al, 2021 , Tahira et al, 2021 ), or loneliness during isolation associated with increased risk of dementia ( Lazzari and Rabottini, 2021 ). Other reviews addressed the impact of the COVID-19 pandemic and isolation on older adults with Alzheimer’s and other types of dementia, including physical deterioration and accelerated ageing ( Lebrasseur et al, 2021 ), changes in neuropsychiatric symptoms of dementia ( Gaigher et al, 2022 , Lebrasseur et al, 2021 , Manca et al, 2020 , Numbers and Brodaty, 2021 , Sánchez-García et al, 2022 , Simonetti et al, 2020 , Suárez-González et al, 2021 ), worsening cognitive health ( Giebel et al, 2022 , Suárez-González et al, 2021 ), as well as new-onset dementia during the first year of COVID-19 isolation ( Suárez-González et al, 2021 ). Although, worsening or new-onset cognitive impairment and subjective mental health deterioration are considered a precursor to dementia, proportions of older adults with dementia and HC experiencing these symptoms for the two-year-and-a-half pandemic period is not well understood.…”
Section: Introductionmentioning
confidence: 99%